Research progress on biochar-based material adsorption and removal of ibuprofen - Zhan, Dan; Ye, Aihui; Hou, Tingting (Frontiers in Environmental Science, 2023)
Ibuprofen, commonly used for pain relief, inflammation, and to reduce high fever, etc., is a widely available over-the-counter drug. In recent years, due to the excessive use of ibuprofen, its presence in the aquatic environments has shown a significant increasing trend, raising concerns about potential risks to environmental safety, which attracted people's close attention. Notably, biochar, known as an environmentally friendly functional material, had been widely studied and applied for the removal of ibuprofen in water environments.According to current reports, the adsorption capacity value of biochar for IBP is between 9.69-309mg/g, and the adsorption mechanism mainly includes π-π stacking, hydrogen bonding, pore filling, etc. In response to this research hotspot, this study reviewed the most recent research progress on the adsorption of ibuprofen using biochar-based materials, including the modified preparation process of biochar and the adsorption mechanism of IBP on various modified biochar surfaces. Additionally, potential challenges and future development directions for the practical applications of biochar were discussed and proposed.